Multifunctional high-temperature wave-absorbing coating and preparation method thereof
Patent Information
- Application Number
- CN202611454695.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-23
AI Technical Summary
解决现有涂层无法协同实现热障、吸波和自愈合多重功能,或功能单一或协同性差的主要问题
1、本多功能高温吸波涂层的过渡层与基体的热膨胀系数差异较小,可适配多种基体,解决层间应力问题;自愈合吸波层中基体相为具有烧绿石结构的改性稀土钛酸盐,具有本征的氧空位形成倾向,从而产生大量氧空位;稳定剂通过少量掺杂也会显著生成大量氧空位,基体相与稳定剂复合后的自愈合层总氧空位浓度保持高位,为愈合提供充足活性位点,具体而言,其自愈合机制基于缺陷化学原理:A位或B位的低价阳离子掺杂(如Mg2+取代Gd3+)会在RE2Ti2O7晶格中引入高浓度的带正电的氧空位。当涂层产生裂纹时,这些氧空位作为活性位点,通过静电力优先吸附并解离从环境渗入的氧分子,解离后的氧原子填充氧空位。该反应导致局部晶格重构和体积膨胀,从而闭合裂纹。由于氧空位是均匀分布的本征缺陷,愈合过程中不会产生低熔点玻璃相等二次相,确保了涂层在高温下的结构稳定性和低热导率。
Smart Images

Figure CN122959654A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-temperature protective coating technology, specifically to a multifunctional high-temperature microwave absorbing coating and its preparation method. Background Technology
[0002] High-temperature protective coating materials need to operate reliably for a long time in environments with high temperature, oxidation, corrosion, and complex electromagnetic waves. Currently, the service environment of hot-end components of extreme high-temperature equipment is becoming increasingly harsh, and existing coating systems have significant technical shortcomings: for example, the traditional thermal barrier coating 8YSZ only has thermal insulation capabilities, and it undergoes phase transformation cracking above 1170℃, lacking wave absorption and self-healing functions; existing self-healing coatings rely on glass phases, such as B2O3-SiO2 or oxidative expansion, the former leading to an increase in thermal conductivity of more than 30%, and the latter having an uncontrollable oxidation rate, neither of which can synergistically achieve multiple functions such as thermal barrier absorption; or they utilize oxygen vacancies to improve the ionic conductivity of ceramics, or act as wave absorbers, but no research has ever used high-concentration oxygen vacancies as a unified microscopic design method to simultaneously achieve crack self-healing and broadband electromagnetic wave absorption.
[0003] Existing technologies are mostly limited to a single substrate and cannot be adapted to multiple novel high-temperature substrate materials simultaneously. Furthermore, coatings with gradient structures suffer from low bonding strength due to interlayer thermal stress, making them prone to peeling. Therefore, there is an urgent need to develop a multifunctional coating to address issues such as high-temperature oxidation, crack propagation, and electromagnetic wave absorption performance failure in critical components or multiple substrates operating at temperatures above 1000°C in aero-engine turbine blades, gas turbine combustors, rocket engine nozzles, and hot-end components of advanced nuclear energy devices. This coating should be suitable for various substrates, providing integrated protection with thermal barrier, self-healing, and electromagnetic wave absorption capabilities. Summary of the Invention
[0004] This invention provides a multifunctional high-temperature microwave absorbing coating and its preparation method. By constructing a multifunctional coating rich in oxygen vacancies, the high concentration of oxygen vacancies in the coating plays a dual role: on the one hand, it achieves a self-healing function, actively capturing and consuming oxygen to repair cracks; on the other hand, it achieves a polarization loss function, generating strong dipole relaxation loss in an electromagnetic field, thereby achieving broadband microwave absorption. This solves the main problem that existing coatings cannot synergistically achieve multiple functions of thermal barrier, microwave absorption, and self-healing, or have only one function or poor synergy.
[0005] This invention provides the following technical solution: a multifunctional high-temperature microwave absorbing coating, comprising a transition layer and a self-healing microwave absorbing layer sequentially from the substrate outwards. The substrate is a nickel-based high-temperature alloy, TiAl and Mo-Si-B alloy, or SiC / SiC composite material; the transition layer is a NiCrAlY-SiC composite transition layer, TiN, ZrN, or Si3N4 transition layer; the self-healing microwave absorbing layer is composed of a matrix phase and a stable phase; the matrix phase is a doped and modified rare-earth titanate with the general molecular formula RE. 2-xA x Ti2O7 or RE2Ti 2-y B y O7, where 0.05≤x≤0.15, 0.03≤y≤0.1, RE is Gd, Nd, Sm, Dy or Ho, A is Mg, Ca, Sr, Ba, Pb or Ni, and B is Cr, Fe, Co, Mn, Al, Ga, In, Sc or Lu; the stable phase is doped and modified hafnium dioxide, with the molecular formula Hf 1-z M z O2, where M is Y, Sc, Gd, Dy or Er, 0.05≤z≤0.25.
[0006] The multifunctional high-temperature absorbing coating employs a gradient structure consisting of a transition layer and a self-healing absorbing layer, making it suitable for various substrates. The self-healing absorbing layer utilizes a composite structure composed of a matrix phase and a stabilizer. The matrix phase is generated by doping rare-earth titanates and metal oxides, providing the main structural framework and intrinsic oxygen vacancies. The stabilizer not only generates a large number of oxygen vacancies itself, but more importantly, its high ionic conductivity promotes the rapid migration and enrichment of oxygen vacancies at crack sites, significantly improving healing efficiency. Simultaneously, the heterogeneous interface formed between the two phases introduces additional interfacial polarization losses, enhancing the absorbing performance.
[0007] As an optional embodiment of the multifunctional high-temperature absorbing coating described in this invention, the substrate is a nickel-based high-temperature alloy, and the transition layer is a NiCrAlY-SiC composite transition layer with a thickness of 60-120 μm. Alternatively, the substrate is a TiAl and Mo-Si-B alloy, and the transition layer is a TiN or ZrN transition layer with a thickness of 30-60 μm. When the substrate is a SiC / SiC composite material, the transition layer is a Si3N4 transition layer with a thickness of 30-60 μm.
[0008] A method for preparing a multifunctional high-temperature microwave absorbing coating includes: Step 1: Weigh the rare earth titanate and metal oxide A or B according to the molecular formula of the matrix phase, and then obtain the ion-doped pre-sintered RE through processes such as mixing and ball milling, drying, grinding, sieving, high-temperature pre-sintering, grinding, and sieving. 2- x A x Ti2O7 or RE2Ti 2-y B y O7 matrix phase ceramic powder; Step 2: Weigh the raw materials according to a mass ratio of HfO2 to rare earth oxides of 5-35:1, and then proceed through a process of mixing, ball milling, drying, grinding, sieving, high-temperature pre-sintering, grinding, and sieving to obtain ion-doped pre-sintered HfO2. 1-z M z O2-stabilized phase ceramic powder; Step 3: Mix the pre-sintered matrix ceramic powder obtained in Step 1 with the pre-sintered stable ceramic powder obtained in Step 2 at a mass ratio of (7-9):(3-1) until homogeneous. Step 4: Select the substrate for grinding, cleaning and preheating, and select the matching transition layer material according to the substrate type; Step 5: Place the transition layer material and the powder mixed in Step 3 into the spray gun in sequence, and then perform plasma spraying on the transition layer and the self-healing microwave absorbing layer in sequence. Step 6: Anneal the coated workpiece in Ar gas or air after spraying.
[0009] As an optional solution to the multifunctional high-temperature absorbing coating preparation method of the present invention, wherein: In step 1, the rare earth titanates are Gd₂Ti₂O₇, Nd₂Ti₂O₇, Sm₂Ti₂O₇, Dy₂Ti₂O₇, and Ho₂Ti₂O₇; the metal oxides are MgO, CaO, SrO, BaO, PbO, NiO, Cr₂O₃, Fe₂O₃, Co₂O₃, Mn₂O₃, Al₂O₃, Ga₂O₃, In₂O₃, Sc₂O₃, and Lu₂O₃. During pre-sintering, the temperature is 1350-1550℃, and the holding time is 4-10 hours.
[0010] In step 2, the rare earth oxides are Y₂O₃, Sc₂O₃, Gd₂O₃, Dy₂O₃, and Er₂O₃. During pre-sintering, the temperature is 1200-1400℃, and the holding time is 2-6 hours.
[0011] In step 5, the distance between the spray gun and the substrate surface is 90-120mm. Spraying is carried out under the conditions of preset spraying power, main gas argon flow rate and auxiliary gas argon / helium / nitrogen flow rate, and the total coating thickness is 1.5-2mm.
[0012] In step 6, annealing is carried out at a temperature of 800-1000℃ and held for 1-2 hours.
[0013] The present invention has the following beneficial effects: 1. The transition layer of this multifunctional high-temperature microwave absorbing coating has a small difference in thermal expansion coefficients with the substrate, making it adaptable to various substrates and solving the interlayer stress problem. The matrix phase in the self-healing microwave absorbing layer is a modified rare-earth titanate with a pyrochlore structure, which has an intrinsic tendency to form oxygen vacancies, thus generating a large number of oxygen vacancies. The stabilizer also generates a large number of oxygen vacancies significantly through a small amount of doping. The total oxygen vacancy concentration of the self-healing layer after the matrix phase and stabilizer are combined remains high, providing sufficient active sites for healing. Specifically, its self-healing mechanism is based on the defect chemistry principle: low-valence cation doping at the A-site or B-site (such as Mg). 2+ Replace Gd 3+This process introduces a high concentration of positively charged oxygen vacancies into the RE2Ti2O7 lattice. When cracks form in the coating, these oxygen vacancies act as active sites, preferentially adsorbing and dissociating oxygen molecules that have infiltrated from the environment through electrostatic forces. The dissociated oxygen atoms then fill the vacancies. This reaction leads to local lattice reconstruction and volume expansion, thereby closing the crack. Because oxygen vacancies are uniformly distributed intrinsic defects, no secondary phases such as low-melting-point glass phases are generated during the healing process, ensuring the structural stability and low thermal conductivity of the coating at high temperatures.
[0014] 2. This multifunctional high-temperature absorbing coating relies on multiple components to generate more complex defect chemistry, achieving synergy between different concentrations of oxygen vacancies and multiple polarization mechanisms. This is an advanced strategy for achieving ultra-wideband absorption. Among them, oxygen vacancies act as dipoles, and their directional alignment under microwave fields generates dielectric loss. The dielectric difference between the matrix phase and the stabilizer will induce interfacial polarization, thereby increasing the overall polarization relaxation loss. Moreover, the absorption performance does not decay after the coating undergoes a healing process, and the absorption bandwidth is ≥8GHz with a reflection loss ≤-5dB in the 8-18GHz band.
[0015] 3. The low thermal conductivity advantage of this multifunctional high-temperature absorbing coating stems from the synergistic effect of phonon scattering and oxygen vacancy scattering. The atomic mass difference between the matrix phase and the stabilizer enhances phonon scattering. Furthermore, the high concentration of oxygen vacancies in the coating generates a high scattering cross section for phonons, resulting in a thermal conductivity ≤3.0 W•m at 1000℃. -1 •K -1 Simultaneously, the healing process does not result in the formation of new phases, and the thermal conductivity exhibits excellent long-term stability. Attached Figure Description
[0016] Figure 1 This is a graph showing the actual radar reflection curve of the multifunctional coating in Example 1 of this application within the range of 2-18 GHz, measured by the bow method at a temperature of 1000°C.
[0017] Figure 2 This is a morphological image showing the changes in micro-cracks on the surface of the multifunctional coating before and after healing in Example 1 of this application. Detailed Implementation
[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] To make the technical solution of this application clearer, the following eight embodiments are used to verify the practicality of this application, covering different matrix and material combinations, and the purity of the raw materials is ≥99%.
[0020] In this application, a high-temperature vector network analyzer was used to test the reflection loss of the coating in the 8-18 GHz frequency band using the bow method in an air environment at 1000℃. The absorption bandwidth was defined as the continuous frequency range with a reflection loss ≤ -5dB. This threshold is suitable for evaluating the engineering absorption performance of the coating in an extreme high-temperature broadband range. The thermal diffusivity of the coating was measured using the laser scintillation method, and the thermal conductivity at 1000℃ was calculated by combining the specific heat capacity and density measured by differential scanning calorimetry. The coated sample was placed in a high-temperature atmosphere furnace and heated to 1000℃ and held for 30 min, and then rapidly cooled to room temperature using a fan. This was one cycle, and the appearance of the coating surface was observed for any peeling or defects.
[0021] Example 1: The substrate is a nickel-based superalloy, and the transition layer is NiCrAlY-SiC.
[0022] Step 1: Weigh Gd₂Ti₂O₇ and MgO in a mass ratio of 150:1, mix and ball-mill, dry, grind, and sieve. Then, heat the sieved powder in a muffle furnace to 1500℃ at a rate of 5℃ / min and hold for 6 hours to generate Mg. 2+ Doped pre-sintered Gd 2-x Mg x Ti2O7 matrix ceramic bulk material was then ground into powder, sieved, and Gd was obtained. 2-x Mg x Ti2O7 matrix ceramic powder; Step 2: Weigh HfO2 and Y2O3 in a mass ratio of 25:1, mix and ball-mill, dry, grind, and sieve. Heat the mixture in a muffle furnace to 1300℃ at a rate of 5℃ / min and hold for 4 hours to generate Y2O3. 3+ Doped pre-sintered Hf 1-z Y z O2-stabilized ceramic blocks were then ground into powder, sieved, and Hf was obtained. 1-z Y z O2-stabilized phase ceramic powder; Step 3: Add Gd 2-x Mg x Ti2O7 matrix phase and Hf 1-z Y z The O2 stable phase was mechanically mixed at a mass ratio of 8:2, the mixer speed was 150 r / min, and the mixing time was 2 h. Step 4: Grind the nickel-based superalloy substrate to a roughness of Ra=5.0μm, then ultrasonically clean it with acetone-ethanol for 15min and preheat it to 350℃. Select NiCrAlY-SiC as the transition layer material. Step 5: Add NiCrAlY-SiC powder and Gd 2-x Mgx Ti2O7 matrix phase and Hf 1-z Y z The mixed powder composed of O2 stable phase is placed in the spray gun in sequence, and the distance between the spray gun and the substrate surface is 100mm; Step 6: Set the spraying power of the NiCrAlY-SiC transition layer to 75kW, the main gas Ar flow rate to 35SLPM, the auxiliary gas to a H2 / He / N2 mixture with a flow rate of 10SLPM, and the spraying thickness to 100μm. Set the spraying power of the self-healing microwave absorbing layer to 80kW, the main gas Ar flow rate to 35SLPM, the auxiliary gas He flow rate to 15SLPM, and the total thickness of the sprayed coating to 1.7mm. Step 7: Place the workpiece in a high-temperature atmosphere furnace, heat it to 1000℃ in Ar gas at a rate of 5℃ / min and hold it for 2 hours, then cool it to room temperature with the furnace to obtain the final product.
[0023] Example 2: The substrate is a nickel-based high-temperature alloy, and the transition layer is NiCrAlY-SiC.
[0024] Step 1: Weigh Gd₂Ti₂O₇ and Cr₂O₃ in a mass ratio of 150:1, mix and ball-mill, dry, grind, and sieve. Then, heat the sieved powder in a muffle furnace to 1500℃ at a rate of 5℃ / min and hold for 6 hours to generate Cr₂O₇. 3+ Doped pre-sintered Gd2Ti 2-y Cr y O7 matrix ceramic bulk material was then ground into powder and sieved to obtain Gd2Ti. 2-y Cr y O7 matrix phase ceramic powder; Step 2: Weigh HfO2 and Y2O3 in a mass ratio of 25:1, mix and ball-mill, dry, grind, and sieve. Heat the mixture in a muffle furnace to 1300℃ at a rate of 5℃ / min and hold for 4 hours to generate Y2O3. 3+ Doped pre-sintered Hf 1-z Y z O2-stabilized ceramic blocks were then ground into powder, sieved, and Hf was obtained. 1-z Y z O2-stabilized phase ceramic powder; Step 3: Add Gd2Ti 2-y Cr y O7 matrix phase and Hf 1-z Y z The O2 stable phase was mechanically mixed at a mass ratio of 8:2, the mixer speed was 150 r / min, and the mixing time was 2 h. Step 4: Grind the nickel-based superalloy substrate to a roughness of Ra=5.0μm, then ultrasonically clean it with acetone-ethanol for 15min and preheat it to 350℃. Select NiCrAlY-SiC as the transition layer material. Step 5: Combine NiCrAlY-SiC powder with Gd2Ti 2-y Cr y O7 matrix phase and Hf 1-z Y z The mixed powder composed of O2 stable phase is placed in the spray gun in sequence, and the distance between the spray gun and the substrate surface is 100mm; Step 6: Set the spraying power of the NiCrAlY-SiC transition layer to 75kW, the main gas Ar flow rate to 35SLPM, the auxiliary gas to a H2 / He / N2 mixture with a flow rate of 10SLPM, and the spraying thickness to 100μm. Set the spraying power of the self-healing microwave absorbing layer to 80kW, the main gas Ar flow rate to 35SLPM, the auxiliary gas He flow rate to 15SLPM, and the total spraying thickness to 1.7mm. Step 7: Place the workpiece in a high-temperature atmosphere furnace, heat it to 1000℃ in Ar gas at a rate of 5℃ / min, hold it at that temperature for 2 hours, and then cool it to room temperature with the furnace to obtain the final product.
[0025] Example 3: The matrix is TiAl and the transition layer is TiN.
[0026] Step 1: Weigh Nd₂Ti₂O₇ and CaO in a mass ratio of 100:1, mix and ball-mill, dry, grind, and sieve. Then, heat the sieved powder in a muffle furnace to 1350℃ at a rate of 2℃ / min and hold for 4 hours to generate Ca. 2+ Doped pre-sintered Nd 2-x Ca x Ti2O7 matrix ceramic bulk material was then ground into powder, sieved, and Nd was obtained. 2-x Ca x Ti2O7 matrix ceramic powder; Step 2: Weigh HfO2 and Sc2O3 in a mass ratio of 5:1, mix and ball-mill, dry, grind, and sieve. Heat the mixture in a muffle furnace to 1200℃ at a rate of 2℃ / min and hold for 6 hours to generate Sc. 3+ Doped pre-sintered Hf 1-z Sc z O2-stabilized ceramic blocks were then ground into powder, sieved, and Hf was obtained. 1-z Sc z O2-stabilized phase ceramic powder; Step 3: Place Nd 2-x Ca x Ti2O7 matrix phase and Hf 1-z Sc zThe O2 stable phase was mechanically mixed at a mass ratio of 7:3, the mixer speed was 150 r / min, and the mixing time was 3 h. Step 4: Grind the TiAl matrix to a roughness of Ra=4.5μm, then ultrasonically clean it with acetone-ethanol for 15min and preheat it to 400℃. Select TiN as the transition layer material. Step 5: Add TiN powder and Nd... 2-x Ca x Ti2O7 matrix phase and Hf 1-z Sc z The mixed powder composed of O2 stable phase is placed in the spray gun in sequence, and the distance between the spray gun and the substrate surface is 90mm; Step 6: Set the spraying power of the TiN transition layer to 65kW, the main gas Ar flow rate to 40SLPM, the auxiliary gas to a mixture of H2 / He / N2 with a flow rate of 10SLPM, and the spraying thickness to 60μm. Set the spraying power of the self-healing microwave absorbing layer to 75kW, the main gas Ar flow rate to 40SLPM, the auxiliary gas He flow rate to 15SLPM, and the total thickness of the sprayed coating to 1.6mm. Step 7: Place the workpiece in a high-temperature atmosphere furnace, heat it to 800°C in Ar gas at a rate of 2°C / min, hold it at that temperature for 2 hours, and then cool it to room temperature with the furnace.
[0027] Example 4: The matrix is TiAl and the transition layer is TiN.
[0028] Step 1: Weigh Nd₂Ti₂O₇ and Fe₂O₃ in a mass ratio of 100:1, mix and ball-mill, dry, grind, and sieve. Then, heat the sieved powder in a muffle furnace to 1350℃ at a rate of 2℃ / min and hold for 4 hours to generate Fe. 3+ Doped pre-sintered Nd2Ti 2-y Fe y O7 matrix ceramic bulk material was then ground into powder and sieved to obtain Nd2Ti. 2-y Fe y O7 matrix phase ceramic powder; Step 2: Weigh HfO2 and Sc2O3 in a mass ratio of 5:1, mix and ball-mill, dry, grind, and sieve. Heat the mixture in a muffle furnace to 1200℃ at a rate of 2℃ / min and hold for 6 hours to generate Sc. 3+ Doped pre-sintered Hf 1-z Sc z O2-stabilized ceramic blocks were then ground into powder, sieved, and Hf was obtained. 1-z Sc z O2-stabilized phase ceramic powder; Step 3: Add Nd2Ti 2-y Fe y O7 matrix phase and Hf1-z Sc z The O2 stable phase was mechanically mixed at a mass ratio of 7:3, the mixer speed was 150 r / min, and the mixing time was 3 h. Step 4: Grind the TiAl matrix to a roughness of Ra=4.5μm, then ultrasonically clean it with acetone-ethanol for 15min and preheat it to 400℃. Select TiN as the transition layer material. Step 5: Mix TiN powder and Nd2Ti 2-y Fe y O7 matrix phase and Hf 1-z Sc z The mixed powder composed of O2 stable phase is placed in the spray gun in sequence, and the distance between the spray gun and the substrate surface is 90mm; Step 6: Set the spraying power of the TiN transition layer to 65kW, the main gas Ar flow rate to 40SLPM, the auxiliary gas to a mixture of H2 / He / N2 with a flow rate of 10SLPM, and the spraying thickness to 60μm. Set the spraying power of the self-healing microwave absorbing layer to 75kW, the main gas Ar flow rate to 40SLPM, the auxiliary gas He flow rate to 15SLPM, and the total thickness of the sprayed coating to 1.6mm. Step 7: Place the workpiece in a high-temperature atmosphere furnace, heat it to 800°C in Ar gas at a rate of 2°C / min, hold it at that temperature for 2 hours, and then cool it to room temperature with the furnace.
[0029] Example 5: The substrate is SiC / SiC, and the transition layer is Si3N4.
[0030] Step 1: Weigh Sm₂Ti₂O₇ and SrO in a mass ratio of 50:1, mix and ball-mill, dry, grind, and sieve. Then, heat the sieved powder in a muffle furnace to 1550℃ at a rate of 3℃ / min and hold for 2 hours to generate SrO. 2+ Doped pre-sintered Sm 2- x Sr x Ti2O7 matrix ceramic bulk material was then ground into powder, sieved, and Sm was obtained. 2-x Sr x Ti2O7 matrix ceramic powder; Step 2: Weigh HfO2 and Gd2O3 in a mass ratio of 20:1, mix and ball-mill, dry, grind, and sieve. Heat the mixture in a muffle furnace to 1400℃ at a rate of 3℃ / min and hold for 2 hours to generate Gd. 3+ Doped pre-sintered Hf 1-z Gd z O2-stabilized ceramic blocks were then ground into powder, sieved, and Hf was obtained. 1-z Gd z O2-stabilized phase ceramic powder; Step 3: Add Sm2-x Sr x Ti2O7 matrix phase and Hf 1-z Gd z The O2 stable phase was mechanically mixed at a mass ratio of 7:3, the mixer speed was 200 r / min, and the mixing time was 4 h. Step 4: Grind the SiC / SiC composite matrix to a roughness of Ra=5μm, then ultrasonically clean it with acetone-ethanol for 20min and preheat it to 320℃. Select Si3N4 as the transition layer material. Step 5: Add Si3N4 powder and Sm... 2-x Sr x Ti2O7 matrix phase and Hf 1-z Gd z The mixed powder composed of O2 stable phase is placed in the spray gun in sequence, and the distance between the spray gun and the substrate surface is 100mm; Step 6: Set the spraying power of the Si3N4 transition layer to 75kW, the main gas Ar flow rate to 40SLPM, the auxiliary gas to a mixture of H2 / He / N2 with a flow rate of 12SLPM, and the spraying thickness to 45μm. Set the spraying power of the self-healing microwave absorbing layer to 90kW, the main gas Ar flow rate to 45SLPM, the auxiliary gas He flow rate to 25SLPM, and the total thickness of the sprayed coating to 2.0mm. Step 7: Place the workpiece in a high-temperature atmosphere furnace, heat it to 900℃ at a rate of 2℃ / min, hold it at that temperature for 2 hours, and then cool it to room temperature with the furnace.
[0031] Example 6: The substrate is SiC / SiC, and the transition layer is Si3N4.
[0032] Step 1: Weigh Sm2Ti2O7 and Co2O3 in a mass ratio of 50:1, mix and ball-mill, dry, grind, and sieve. Then, heat the sieved powder in a muffle furnace to 1550℃ at a rate of 3℃ / min and hold for 2 hours to generate Co. 3+ Doped pre-sintered Sm2Ti 2-y Co y O7 matrix ceramic bulk material was then ground into powder and sieved to obtain Sm2Ti. 2-y Co y O7 matrix phase ceramic powder; Step 2: Weigh HfO2 and Gd2O3 in a mass ratio of 20:1, mix and ball-mill, dry, grind, and sieve. Heat the mixture in a muffle furnace to 1400℃ at a rate of 3℃ / min and hold for 2 hours to generate Gd. 3+ Doped pre-sintered Hf 1-z Gd z O2-stabilized ceramic blocks were then ground into powder, sieved, and Hf was obtained. 1-z Gdz O2-stabilized phase ceramic powder; Step 3: Add Sm2Ti 2-y Co y O7 matrix phase and Hf 1-z Gd z The O2 stable phase was mechanically mixed at a mass ratio of 7:3, the mixer speed was 200 r / min, and the mixing time was 4 h. Step 4: Grind the SiC / SiC composite matrix to a roughness of Ra=5μm, then ultrasonically clean it with acetone-ethanol for 20min and preheat it to 320℃. Select Si3N4 as the transition layer material. Step 5: Combine Si3N4 powder and Sm2Ti 2-y Co y O7 matrix phase and Hf 1-z Gd z The mixed powder composed of O2 stable phase is placed in the spray gun in sequence, and the distance between the spray gun and the substrate surface is 100mm; Step 6: Set the spraying power of the Si3N4 transition layer to 75kW, the main gas Ar flow rate to 40SLPM, the auxiliary gas to a mixture of H2 / He / N2 with a flow rate of 12SLPM, and the spraying thickness to 45μm. Set the spraying power of the self-healing microwave absorbing layer to 90kW, the main gas Ar flow rate to 45SLPM, the auxiliary gas He flow rate to 25SLPM, and the total thickness of the sprayed coating to 2.0mm. Step 7: Place the workpiece in a high-temperature atmosphere furnace, heat it to 900°C in air at a rate of 2°C / min, hold it at that temperature for 2 hours, and then cool it to room temperature with the furnace.
[0033] Example 7: The matrix is selected as Mo-Si-B alloy, and the transition layer is selected as ZrN.
[0034] Step 1: Weigh Dy2Ti2O7 and BaO in a mass ratio of 200:1, mix and ball-mill, dry, grind, and sieve. Then, heat the sieved powder in a muffle furnace to 1500℃ at a rate of 4℃ / min and hold for 3 hours to produce BaO. 2+ Doped pre-sintered Dy 2-x Ba x Ti2O7 matrix ceramic bulk material was then ground into powder, sieved, and Dy was obtained. 2-x Ba x Ti2O7 matrix ceramic powder; Step 2: Weigh HfO2 and Er2O3 in a mass ratio of 35:1, mix and ball-mill, dry, grind, and sieve. Heat the mixture in a muffle furnace to 1250℃ at a rate of 4℃ / min and hold for 3 hours to generate Er2O3. 3+ Doped pre-sintered Hf 1-z Er zO2-stabilized ceramic blocks were then ground into powder, sieved, and Hf was obtained. 1-z Er z O2-stabilized phase ceramic powder; Step 3: Dy 2-x Ba x Ti2O7 matrix phase and Hf 1-z Er z The O2 stable phase was mechanically mixed at a mass ratio of 9:1, the mixer speed was 200 r / min, and the mixing time was 4 h. Step 4: Grind the Mo-Si-B alloy substrate to a roughness of Ra=3μm, then ultrasonically clean it with acetone-ethanol for 20min and preheat it to 380℃. Select ZrN as the transition layer material. Step 5: Add ZrN powder and Dy 2-x Ba x Ti2O7 matrix phase and Hf 1-z Er z The mixed powder composed of O2 stable phase is placed in the spray gun in sequence, and the distance between the spray gun and the substrate surface is 120mm; Step 6: Set the spraying power of the ZrN transition layer to 65kW, the main gas Ar flow rate to 45SLPM, the auxiliary gas to a mixture of H2 / He / N2 with a flow rate of 8SLPM, and the spraying thickness to 60μm. Set the spraying power of the self-healing microwave absorbing layer to 85kW, the main gas Ar flow rate to 35SLPM, the auxiliary gas He flow rate to 25SLPM, and the total thickness of the sprayed coating to 1.5mm. Step 7: Place the workpiece in a high-temperature atmosphere furnace, heat it to 1100℃ at a rate of 2℃ / min, hold it at that temperature for 1 hour, and then cool it to room temperature with the furnace.
[0035] Example 8: The matrix is selected as Mo-Si-B alloy, and the transition layer is selected as ZrN.
[0036] Step 1: Weigh Dy2Ti2O7 and Mn2O3 in a mass ratio of 200:1, mix and ball-mill, dry, grind, and sieve. Then, heat the sieved powder in a muffle furnace to 1500℃ at a rate of 4℃ / min and hold for 3 hours to generate Mn. 3+ Doped pre-sintered Dy2Ti 2-y Mn y O7 matrix ceramic bulk material was then ground into powder and sieved to obtain Dy2Ti. 2-y Mn y O7 matrix phase ceramic powder; Step 2: Weigh HfO2 and Er2O3 in a mass ratio of 35:1, mix and ball-mill, dry, grind, and sieve. Heat the mixture in a muffle furnace to 1250℃ at a rate of 4℃ / min and hold for 3 hours to generate Er2O3. 3+Doped pre-sintered Hf 1-z Er z O2-stabilized ceramic blocks were then ground into powder, sieved, and Hf was obtained. 1-z Er z O2-stabilized phase ceramic powder; Step 3: Add Dy2Ti 2-y Mn y O7 matrix phase and Hf 1-z Er z The O2 stable phase was mechanically mixed at a mass ratio of 9:1, the mixer speed was 200 r / min, and the mixing time was 4 h. Step 4: Grind the Mo-Si-B alloy substrate to a roughness of Ra=3μm, then ultrasonically clean it with acetone-ethanol for 20min and preheat it to 380℃. Select ZrN as the transition layer material. Step 5: Combine ZrN powder and Dy2Ti 2-y Mn y O7 matrix phase and Hf 1-z Er z The mixed powder composed of O2 stable phase is placed in the spray gun in sequence, and the distance between the spray gun and the substrate surface is 120mm; Step 6: Set the spraying power of the ZrN transition layer to 65kW, the main gas Ar flow rate to 45SLPM, the auxiliary gas to a mixture of H2 / He / N2 with a flow rate of 8SLPM, and the spraying thickness to 60μm. Set the spraying power of the self-healing microwave absorbing layer to 85kW, the main gas Ar flow rate to 35SLPM, the auxiliary gas He flow rate to 25SLPM, and the total thickness of the sprayed coating to 1.5mm. Step 7: Place the workpiece in a high-temperature atmosphere furnace, heat it to 1100℃ at a rate of 2℃ / min, hold it at that temperature for 1 hour, and then cool it to room temperature with the furnace.
[0037] Table 1 shows the main properties of the multifunctional coatings in Examples 1-8 measured at 1000°C:
[0038] Performance tests were conducted on the multifunctional high-temperature absorbing coatings prepared in the above embodiments, and it was determined that: the coatings in Examples 1-8, under an oxygen-containing environment at 1000℃, all exhibited an absorption bandwidth (≤-5dB) ≥8GHz in the 8-18GHz band, and a thermal conductivity <3.0 W•m. -1 •K -1 The coatings showed no significant changes in appearance or peeling after 500 thermal shock cycles. When cracks and voids appeared in the coating, after heat treatment at 800-1100℃ and holding for 1-4 hours, the microscopic surface healing effect of the coating was observed to be good (see attached figure). Figure 2The above results demonstrate that the multifunctional high-temperature absorbing coating in this application possesses multiple properties, including thermal barrier, wave absorption, and self-healing capabilities. Figure 1 As shown, the coating in Example 1 has an absorption bandwidth of 8.5 GHz in the 8-18 GHz band, while Figure 2 The results show that after annealing at 1000℃, the microcracks on the coating surface have been largely healed.
[0039] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0040] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A multifunctional high-temperature microwave absorbing coating, characterized in that, From the substrate outwards, it includes a transition layer and a self-healing microwave absorbing layer. The matrix is a nickel-based superalloy, TiAl and Mo-Si-B alloy or SiC / SiC composite material; The transition layer is a NiCrAlY-SiC composite transition layer, TiN, ZrN, or Si3N4 transition layer; The self-healing absorbing layer consists of a matrix phase and a stable phase; the matrix phase is a doped and modified rare-earth titanate with the molecular formula RE. 2-x A x Ti2O7 or RE2Ti 2-y B y O7, where 0.05≤x≤0.15, 0.03≤y≤0.1, RE is Gd, Nd, Sm, Dy or Ho, A is Mg, Ca, Sr, Ba, Pb or Ni, and B is Cr, Fe, Co, Mn, Al, Ga, In, Sc or Lu; The stable phase is doped and modified hafnium dioxide, with the general molecular formula Hf. 1-z M z O2, where M is Y, Sc, Gd, Dy or Er, 0.05≤z≤0.
25.
2. The multifunctional high-temperature absorbing coating according to claim 1, characterized in that: The matrix is a nickel-based high-temperature alloy, and the transition layer is a NiCrAlY-SiC composite transition layer with a thickness of 60-120μm.
3. The multifunctional high-temperature absorbing coating according to claim 1, characterized in that: The matrix is a TiAl and Mo-Si-B alloy, and the transition layer is a TiN or ZrN transition layer with a thickness of 30-60 μm.
4. The multifunctional high-temperature absorbing coating according to claim 1, characterized in that: The matrix is a SiC / SiC composite material, and the transition layer is a Si3N4 transition layer with a thickness of 30-60μm.
5. A method for preparing a multifunctional high-temperature absorbing coating, used to prepare the multifunctional high-temperature absorbing coating according to any one of claims 1-4, characterized in that: include: Step 1: Weigh the rare earth titanate and metal oxide A or B according to the molecular formula of the matrix phase, then mix, ball mill, dry, grind, sieve, pre-sinter at high temperature, grind, and sieve again to obtain ion-doped pre-sintered RE. 2-x A x Ti2O7 or RE2Ti 2-y B y O7 matrix phase ceramic powder; Step 2: Weigh the raw materials according to a mass ratio of HfO2 to rare earth oxides of 5-35:1, then mix, ball-mill, dry, grind, sieve, pre-sinter at high temperature, grind, and sieve again to obtain ion-doped pre-sintered HfO2. 1-z M z O2-stabilized phase ceramic powder; Step 3: Mix the pre-sintered matrix ceramic powder obtained in Step 1 with the pre-sintered stable ceramic powder obtained in Step 2 at a mass ratio of (7-9):(3-1) until homogeneous. Step 4: Select the substrate for grinding, cleaning and preheating, and select the matching transition layer material according to the substrate type; Step 5: Place the transition layer material and the powder mixed in Step 3 into the spray gun in sequence, and then perform plasma spraying on the transition layer and the self-healing microwave absorbing layer in sequence. Step 6: Anneal the coated workpiece in Ar gas or air after spraying.
6. The method for preparing the multifunctional high-temperature absorbing coating according to claim 5, characterized in that: In step 1, the pre-sintering temperature is 1350-1550℃, and the holding time is 4-10h; In step 2, the pre-sintering temperature is 1200-1400℃, and the holding time is 2-6 hours; In step 5, the distance between the spray gun and the substrate surface is 90-120mm. Spraying is carried out under the conditions of preset spraying power, main gas argon flow rate and auxiliary gas argon / helium / nitrogen flow rate. The total coating thickness is 1.5-2mm. In step 6, annealing is carried out at a temperature of 800-1000℃ and held for 1-2 hours.